A multiplex RT‐PCR for rapid and simultaneous detection of viruses and viroids in chrysanthemum. (2nd November 2012) - Song, A.; You, Y.; Chen, F.; Li, P.; Jiang, J.; Chen, S.
Abstract Chrysanthemum plants are subject to serious virus diseases, so detection and identification of virus pathogens is important to prevent the virus spread. A reliable one‐step multiplex RT‐PCR was developed to simultaneously detect two viruses and two viriods: chrysanthemum virus B, tomato Aspermy virus, chrysanthemum stunt viroid and chrysanthemum chlorotic mottle viroid. In addition, we investigated the detection limit and the efficiency of single and multiplex RT‐PCR assays. The results showed that the multiplex RT‐PCR assay proved to be as sensitive as the single one. In conclusion, this technique is potentially useful in routine diagnosis of chrysanthemum viruses and viroids. Significance and Impact of Study The multiplex RT‐PCR assay described in this study is the first report of simultaneous detection of virus and viroid in chrysanthemum, which provides a fast, convenient, cost‐saving way to detect the virus and viroid mixed infections in plants.